2005
DOI: 10.1111/j.0883-2919.2005.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

"Brain Gain statt[instead of]Brain Drain": the role of English in German education

Abstract: :  Although there is extensive research on Anglicisms in the German language (e.g. Carstensen, 1965; Carstensen, Busse & Schmude, 1993–6; Fink, 1970, 1980, 1995; Görlach, 2002), few studies look beyond lexical borrowing and structural impact to consider other aspects and dimensions of English–German contact in the Federal Republic of Germany. This qualitative study addresses this need in part by examining the role of English in the domain of education. The analysis focuses first on the impact of English in Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 7 publications
(5 reference statements)
2
21
0
Order By: Relevance
“…Recent studies have shown that children are beginning to learn English at earlier ages (e.g. Erling, 2004;Hilgendorf, 2005), a pattern which can also be seen in this study, as 13 per cent of students had started English by the third grade. For the overwhelming majority of students surveyed, German generally was the only medium of instruction in the schools they attended.…”
Section: English At School and Universitysupporting
confidence: 82%
“…Recent studies have shown that children are beginning to learn English at earlier ages (e.g. Erling, 2004;Hilgendorf, 2005), a pattern which can also be seen in this study, as 13 per cent of students had started English by the third grade. For the overwhelming majority of students surveyed, German generally was the only medium of instruction in the schools they attended.…”
Section: English At School and Universitysupporting
confidence: 82%
“…It can be part of the "integrated comparative approach" for pre-service and in-service teacher training courses in Russia put forward in Kolesnikova (2005). It can inform the competence of ESP practitioners working in tertiary education settings or in such settings where English is used as the medium of instruction (e.g., see the descriptions in Hilgendorf 2005). It can offer a training basis for integrating the critical dimension in EAP tutoring proposed by Sarah Benesch (2009).…”
Section: Resultsmentioning
confidence: 99%
“…Education is another domain where one can trace the changing status of English (Hilgendorf 2005, and the references she cites). English instruction in Jordan has a long history and unique prestige in the education system.…”
Section: Introductionmentioning
confidence: 99%